THE PROBLEM OF PERSONALITY IN SOCIAL PSYCHOLOGY (Conferencea, 2022)
The peculiarity of the socio-psychological approach to the problem of personality lies in the fact that it is considered as a consequence of different forms of interaction with different groups. That is, social psychology primarily studies the laws of behavior of a person in a group, and how the influence of a person in the communication system is reflected in his mind.